MANAJEMEN KURIKULUM DALAM MENGINTEGRASIKAN EMPAT PILAR PENDIDIKAN UNESCO SEBAGAI UPAYA MEMBENTUK KARAKTER PESERTA DIDIK DI SD MAMBA’UL HISAN KEDIRI - Akbar, Ahmad Abdal; Maimun, Agus; Ghofur, Abdul (Jurnal Manajemen Pendidikan, 2025)
Penelitian This study aims to analyze curriculum management in integrating the Four Pillars of UNESCO Education as a strategy to develop students’ character at SD Mamba’ul Hisan Kediri. The research employed a qualitative approach with a quasi-qualitative design, combining observation, in-depth interviews, and document analysis to obtain a comprehensive understanding of the planning, implementation, and evaluation of the integrated curriculum. The findings indicate that the school integrates the four pillars learning to know, learning to do, learning to be, and learning to live together through character-based curriculum planning, structured module development, religious habituation, and the strengthening of social interaction within classroom activities. The implementation of this integration is carried out collaboratively by the principal, teachers, and foundation, supported by a religious school culture and a conducive academic environment. The impact is reflected in the improvement of students’ discipline, responsibility, independence, and positive social interaction skills. However, the study also identifies several challenges, including limited facilities, varied teacher competencies in applying student-centered learning, and low motivation among some students. The study concludes that directed and consistent curriculum management significantly contributes to the internalization of character values through the UNESCO Four Pillars.